THE IMPACT OF JAMKESMAS ON HEALTHCARE UTILIZATION IN EASTERN REGIONS OF INDONESIA: A PROPENSITY SCORE MATCHING METHOD - Sambodo, Novat Pugo (Jurnal Ekonomi & Studi Pembangunan, 2018)
Underutilization of health care for the poor is one critical problem in Indonesia. Out of pocket share is dominant on overall health financing. Therefore, it is plausible that low demand of modern healthcare services mainly relates to financial aspect. In 2008, the government of Indonesia has introduced health insurance schemes for the poor to help them overcome the problem of medical costs barrier called Jamkesmas (Social Health Insurance). This paper examines the impact evaluation of Jamkesmas to health care utilization in Eastern Indonesia. Data are drawn from Indonesia Family Life Survey East (IFLS-East) that held in 2012. This data only covers the eastern regions of InÂdonesia that widely known has relatively lower performance in development and infrastructure. Moreover, this study employs Propensity Score Matching (PSM) approach to analyse the data. The results show that average treatment effect for treated group are positive for outpatient utilization. In addition, availability of the healthcare facility variables, travelling time and distance to district capital are factors that determine Jamkemas coverage in Eastern Indonesia.